O português dos Tongas de São Tomé. In Oliveira, Márcia Santos Duarte; Araujo, Gabriel Antunes. (orgs.) O português na Africa atlântica - Baxter, A. N. (Humanitas/FAPESP, 2018)

ARTECH2017: Proceedings of the 8th International Conference on Digital Arts - Caires, Carlos; Cardoso, Jorge Carlos; Lipovka, Aleksei; Bidarra, José; Pimentel, Lúcia (Association for Computing Machinery, 2017)

Jornalismo e Qualidade no Mundo de Expressão Portuguesa - Camponez, Carlos; Simões, José Manuel; Christofoletti, Rogério (University of Saint Joseph, 2022)
"Jornalismo e Qualidade no Mundo de Expressão Portuguesa"propõe uma análise sobre a paisagem do jornalismo nos oitopaíses de língua oficial portuguesa - Portugal, Angola, Brasil, Cabo Verde, Moçambique, Guiné-Bissau, São Tomé e Príncipee Timor-Leste - e na Região Autónoma Especial de Macau. Olivro é uma reflexão sobre a legislação, o plano jurídico-constitucionalque enquadra os media no espaço lusófono, os contextosde mercado, as especificidades inscritas em fatoreshistóricos e económicos, em percursos políticos, bem comosobre as relações entre os media e os jornalistas e estes e opoder regulador do Estado.Os trabalhos reunidos nesta obra escrita por autores que partilhamentre si um dos idiomas mais falados do planeta, mostram as diferentes realidades do jornalismo no espaço dalíngua portuguesa, nomeadamente as suas redes de conhecimento, de empenho na promoção da qualidade da informação, de intercompreensão entre povos e culturas, de novas einovadoras formas de parcerias sociais com vista à partilha e àconstrução de mundividências.

Design Thinking associated with R&D: Process Management and Knowledge Transfer for the Creative Industries - Cerejo, Joana; Barbosa, Álvaro (LAP LAMBERT Academic Publishing, 2014)
The difficult task of innovation is a key facet of Research & Development (R&D) institutions. To Design, innovation is to make the project technically feasible, economically viable, merchandising interesting and emotionally engaging. Design Thinking integrated with R&D organizations can foster the relationship between Universities and new markets. By addressing these topics, this book researches new emerging design methods and provide an overview of Design Thinking tools that can be applied in an early stage of the R&D research process to produce meaningful results. It is taken into account that design, through Design Thinking, extends to the experience that costumers/users have with products/services or even multidimensional experiences, which is a relevant input for R&D innovation development. In fact, the establishment of coherent guidelines for the Design Thinking process is a very complex task, due to its interdisciplinary requirements, that convey many diverse mindsets. The main focus of this book is creating an analysis toolkit that enables non-specialist and specialist users to perform high-quality design solutions.

Interaction design for a contemporary learning and teaching environment: promoting independent learning at the primary level - Chan, Ka Chi (USJ Theses and Dissertations, 2022)
The world is perpetually changing, and the COVID-19 pandemic has taught us that the future is full of unforeseen challenges and potentialities. What are the implications of the advancement in technology on education? How are teachers coping with contemporary educational expectations? Is there a need to redesign the learning environment? What is the exact nature of the forces driving such a change? Is there anything we can learn from successful innovations around the globe? The goals of this dissertation include designing a learning/teaching app and redesigning classroom furniture for primary-level education. A design thinking methodology is used, working through the phases of empathizing, defining, ideating, prototyping and testing the two potential designs
Keywords: Design; Interaction analysis in education; Interactive multimedia

Book of Proceedings of ARTeFACTo 2022 Macao, Third International Conference on Digital Creation in Arts, Media and Technology - Emerging Extended Realities - Estadieu, G; Martins de Abreu, F.; Caires, Carlos; Fernandes Marco, A. (IEEE, 2023)

(Un)directed Reading: Selected Students' Work Directed Reading 2020/21 University of Saint Joseph, Macao, China - Olga Ng Ka Man, Sandra (University of Saint Joseph, 2023)
Keywords: Literature

Book of Proceedings of ARTECH 2021 - 10th International Conference on Digital and Interactive Arts (Hybrid Praxis – Art, Sustainability & Technology) - Lopes, Maria Manuela; Lopes, Paulo Bernardino; Araújo, António; Olivero, Lucas Fabian; Marcos, Adérito Fernandes (2021)

Translation into Portuguese of the work Macau Days - a tri-lingual book (English, Portuguese, Chinese) that includes a series of poetic texts by Brian Castro and artworks by John Young, 2017 in collaboration with the J.M. Coetzee Centre for Creative Practice and the EU Centre for Global Affairs, University of Adelaide, Australia. - Morais, I. (A-A-Publishing, 2018)

De Portugal a Macau: Filosofia e Literatura no Diálogo das Culturas - Natário, Maria Celeste; Espadinha, Maria Antónia (Universidade do Porto, Faculdade de Letras, 2017)

Historical Space in Macao - Pinheiro, Francisco Vizeu (IACM : Jiangnam University, 2016)

Jornalismo multicultural em português: Estudo de caso em Macau - Simões, José Manuel
O ponto central da reflexão da obra é o jornalismo produzido na Região Administrativa Especial de Macau – detentora da maior densidade de media no mundo – em língua portuguesa. O autor discute quais as verdadeiras possibilidades de exercício de um jornalismo livre, isento e responsável não apenas na RAEM, mas também em Portugal, demonstrando que nos dois territórios as ameaças existentes são distintas mas reais, o que se traduz no facto de resultarem da conjugação entre o modelo de jornalismo ocidental e a realidade local.O livro apresenta dados concretos sobre questões que são hoje centrais no mundo da comunicação, aferindo o nível de liberdade permitido aos jornalistas para desenvolverem o seu trabalho numa das regiões administrativas da China, e que suscitam uma dicussão sobre temas específicos do dia-a-dia de Macau, como o convívio de diferentes grupos culturais que, coexistindo no mesmo espaço geográfico, utilizam diferentes canais para disseminar e debater informação no espaço público.

Os índios potiguara: memória, asilo e poder - Simões, José Manuel (Coleção mediaXXI, 2013)

The Inner Harbour - Background Document on the Revitalization of Macau’s Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2014)

The Inner Harbour – Policy Recommendations on the Revitalization of Macau’s Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2014)

The Inner Harbour Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2018)